Airflow Velocity Measurement Of Turbular Test Section Based On Rpm Setting Configuration In Open Circuit Subsonic Wind Tunnel - Syifa Fauziah Rahmani, Nanda; Sugianto, Sugianto; Masruri, Deden (Indonesian Society of Applied Science, 2024)
Speed measurements in the test section based on the RPM setting configuration of the open-type subsonic wind tunnel with a turbular test section to obtain the properties of the airflow in the test section based on the RPM setting configuration in the open-type subsonic wind tunnel. The simulation process is carried out using software Computational Fluid Dynamics (CFD) , ANSYS Fluent. The simulation process is carried out by the method Moving Reference Frame (MRF) that the fluid phenomenon is moved to move the fan in the wind tunnel to obtain airflow properties in the turbular test section, open-type subsonic wind tunnel. In the testing process, airflow velocity measurements were carried out in the turbular test section of the open-type subsonic wind tunnel using an air velocity measuring instrument, namely anemometer and hotwire. The software Computer Aided Design (CAD), Solidworks, serves to create the geometry of the open-type subsonic wind tunnel and has a turbular test section inspired by the Didacta Italia PN21 D open-type subsonic wind tunnel. The properties that occur in the test section based on the configuration of the RPM setting in the open-type subsonic wind tunnel turbular test section are expected to achieve results to obtain the value of the velocity distribution, pressure distribution and turbulence intensity value so that it is useful and supports the operation and testing process to be carried out in an open-type subsonic wind tunnel with a turbular test section.